2017
DOI: 10.2320/jinstmet.jc201702
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Heterogeneous Nano-Structure Developed in Heavily Cold-Rolled Austenitic Stainless Steel on Texture and Ductility

Abstract: SUS316LN austenitic stainless steel was simply and heavily cold-rolled up to 92% reduction in thickness. The microstructure developed was composed of complicated heterogeneous nano-structure; "eye-shaped" twin domains, which were surrounded by shear bands, were embedded in low-angle lamellar boundaries. The cold-rolled austenitic steel exhibited marvelous high strength of 1.95 GPa when tensile tested normal to the rolling direction, while lower strength of 1.57 GPa along the rolling direction. Moderate ductili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…5(a), was estimated to be about 57% distributed over the whole observed area. This value is considerably high compared to that of about 10% in a 92% cold-rolled SUS316LN steel reported by Miura et al 13) They suggested that this low area fraction of the twin domains caused the relatively low tensile strength (less than 2 GPa) of the heavily cold-rolled SUS316LN steel. This was confirmed in the study by Aoyagi et al, in which they revealed that tensile strength increases with the area fraction of twin domain through multi-scale crystal-plastic simulation using crystal information of the HN structures.…”
Section: (B)mentioning
confidence: 61%
See 1 more Smart Citation
“…5(a), was estimated to be about 57% distributed over the whole observed area. This value is considerably high compared to that of about 10% in a 92% cold-rolled SUS316LN steel reported by Miura et al 13) They suggested that this low area fraction of the twin domains caused the relatively low tensile strength (less than 2 GPa) of the heavily cold-rolled SUS316LN steel. This was confirmed in the study by Aoyagi et al, in which they revealed that tensile strength increases with the area fraction of twin domain through multi-scale crystal-plastic simulation using crystal information of the HN structures.…”
Section: (B)mentioning
confidence: 61%
“…On the other hand, the formation of eye-shaped twin domains bearing the {111} < 211 > orientation was reported to suppress the development of the {011} < 112 > sharp rolling texture in the HN structured austenitic steel. 13) Therefore, even after heavy cold rolling, the attained moderate ductility should be affected by the change in the rolling texture, due to the formation of HN structure. Moreover, it should be remarkable that the amount of work hardening (σ UTS -σ 0.2 ) during tensile tests (the inset in Fig.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…23) Miura et al explained the rather good elongation of stainless steel with heterogeneous nano- structure by i) weaken texture, ii) twinning-induced plasticity (TWIP), iii) shear-banding induced plasticity. 11,12) The comparable uniform elongation of the heavily cold-rolled samples with those of the MDFed one should be possibly due to suppression of sharp ©001ª{110} texture 11,12) and TWIP effect. 11) In fact, rather good elongation by TWIP is confirmed in SUS316LN stainless steel with heterogeneous nano-structure.…”
Section: Mechanical Propertiesmentioning
confidence: 93%
“…10,11) It is expected from the above observations of heterogeneous nano-structure, therefore, bendability and ductility would be improved. 12) This will be discussed in detail in the section of 3.3.…”
Section: Microstructure Evolved After Heavy Cold Rollingmentioning
confidence: 99%
See 1 more Smart Citation